Teachers’s Effort in Managing English Class at a Senior High School in Kota Cirebon - Budiana, Haris (Papanda Publisher, 2022)
Classroom management skill is a crucial part of teachers’ figure. Since barriers in achieving learning goals might come up in every classroom learning activity. In this research, the writer investigated the experience of English teachers through interviews for various problems faced during the teaching learning activities and the management process as the teachers’ efforts to create a conducive classroom activities. the participants were the English teachers at school. The method that the researcher used is qualitative whereas the interview was conducted to gain the data. The data analysis proved that the teachers face the unwanted behavior and attitude of students during the class such as lateness or leaving early , side conversations, indifference to teachers’ instruction, cheating, and having meals without permit. Neverthe lesss, the teaching learning activities can be said running well as the teachers cope with such barriers by deploying learning strategies such as work in group, discussion for problem solving, individual communication, trustbuilding , giving chance for self expression, designing challenging and interesting activities. The teachers’ classroom was able to make the classroom activities comfortable for both teachers and students.